Factors Associated with The ‘Dagusibu’ Drug Management Behavior Via Home Pharmacy Care for Community in Central Jakarta District - Adin Hakim Kurniawan; Purnama Fajri (Politeknik Kesehatan Kemenkes Jakarta II, 2020)
The household drug management is common practice worldwide especially Ethical drugs and OTC Drugs that indicated are acute and chronic condition. The beside higher costs, accumulation medicines at home can be attributed to the lack of knowledge and behavior in patient, patient's family and environmental. Negative relationships in household drug management more likely risk for elderly people have many illnesses and polypharmacy, drug interactions and adverse drug reactions. The objective of this study to analyze the factors Associated to behavior Dagusibu drug management in Community Jakarta Pusat With Home Pharmacy Care. This research used observational research by using cross-sectional design. this research type probability sampling with technique is cluster random sampling. The data analysis used bivariate analysis , especially chisquare test. The result of multivariate analysis showed the variable were significantly related to behavior dagusibu drug management, namely variables were medicine dispossal box (p=0.019;OR 3.009); medicine safety box (p=0.025;OR 2.974) and influence efect of family support (p=0.001;OR=5.092).